NEGARA DAN PENDIDIKAN, SENTRALISASI DAN DESENTRALISASI PENDIDIKAN, MANAJEMEN BERBASIS SEKOLAH - Suwardi, Suwardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Thus, as an impact of the centralistic education system, efforts to create education that can give birth to human figures who have freedom of thought, are able to solve problems independently, work and live in creative groups full of initiative and desire, have adequate interpersonal skills as a provision for society. it becomes very difficult to realize. Centralization was widely used by the government before regional autonomy. The weakness of the centralized system is where a local government policy and decision is produced by people who are in the central government so that the time to decide on something is longer. Indonesia as a developing country with various socio-cultural characteristics in common, also follows a centralized system that has long been developed in developing countries. Thus, as an impact of the centralized education system, efforts to create education that can give birth to human figures who have freedom of thought, are able to solve problems independently, work and live in creative groups full of initiative and passion, have adequate interpersonal skills as a provision for society to become very difficult to materialize. As a consequence, the implementation of education in Indonesia is completely uniform, decisions from above, such as a uniform curriculum regardless of the level of relevance to children's lives and their environment. As a consequence, the position and role of students tend to be used as objects so that those who have the opportunity to develop their creativity and interests are in accordance with their talents. The term school-based management is a translation of school-based management. This term first appeared in the United States when people began to question the relevance of education to the demands and development of local communities. SBM is a new paradigm in the world of education, which provides broad autonomy at the school level (community involvement) in the framework of national education policies. Autonomy is given so that schools can freely manage resources and financial resources by allocating them according to priority needs, and are more responsive to local needs.